Cyclodextrin/dextran based hydrogels prepared by cross-linking with sodium trimetaphosphate. (5th November 2015) - Wintgens, Véronique; Lorthioir, Cédric; Dubot, Pierre; Sébille, Bernard; Amiel, Catherine
Highlights: Synthesis of novel β-cyclodextrin/dextran based hydrogels is reported. Sodium trimetaphosphate is used as a cross-linking agent. The phosphated groups endow the hydrogels with interesting swelling properties. Loading and release of probes with different polarities show the potentiality of the hydrogels for drug delivery. Abstract: Novel βCD-based hydrogels have been synthesized using sodium trimetaphosphate (STMP) as non-toxic reagent. Straightforward mixing of βCD with dextran and STMP in basic aqueous media led to hydrogels incorporating dextran chains, phosphate groups and βCD units. The hydrogels have been characterized by swelling measurements, XPS and 31 P NMR. The swelling ratio was correlated to the content in phosphated groups, which give a polyelectrolyte character to these hydrogels. The significant rise of the swelling ratio with the βCD content increase has been attributed to a decrease of the number of phosphate-based crosslinks, the βCD units playing the role of dangling ends in the tridimensional network. Their loading capacity and their release properties have been investigated for methylene blue and benzophenone in order to demonstrate their potentiality for drug delivery. Through different interaction mechanisms, electrostatic and inclusion complex interactions, these compounds are loaded with different efficiencies. The release involves deswelling, diffusion mechanisms and partition equilibrium.